To study the association of body mass index of mother and anthropometry of new born - Karthika, K.; Wagh, Anjali (International Journal Of Community Medicine And Public Health, 2017)
Background: India is now facing a double burden with underweight on one side, and a rapid upsurge in overweight, particularly in the urban settings on the other side. With a maternal mortality rate of 174 per100,000 live births and with an infant mortality rate of 38 per 1000 live births, there is an absolute need to focus upon the health of the mothers and thence that of the new-born. So, we planned to study the correlation between the BMI of the mother with that of the outcome of the pregnancy. Methods: 152 women, who were registered and gave birth in the respective hospitals during the study period were selected randomly and were enrolled for the study. A detailed history was taken on their socio-economic class, obstetric status, diet and body mass index was calculated. And, the anthropometry of the new borns was taken. Results: Mothers with BMI less than normal had babies of low birth weight in major proportion (86%). Mothers with BMI falling under normal range had 13% low birth weight babies. Mothers with BMI more than normal had 55.5% low birth weight babies, 29.6% normal birth weight babies and also around 15% high birth weight babies. Conclusions: There is a definite correlation between the BMI of mother and the anthropometry of the child. Any deviation from the normal body mass index of the mother is seen to be related to a change in the anthropometry of the newborn.